Information Disorder Learning to Recognize Fake News - Biondo, Francesco; La Rocca, Gevisa; Viviana Trapani, Viviana (Peter Lang International Academic Publishers, 2022)
The Smart Specialisation Strategy (RIS3), namely the national or regional innovation strategies for smart, sustainable and inclusive growth in the European Union, co-funded by the European Commission, with the general objective of concentrating European resources on emerging technology areas that can be developed in the region by focusing on building local knowledge rather than transferring external technological resources. The Sicily Region, with the ERDF Operational Programme 2014-2020, Action 1.1.5 for "Support for the technological advancement of companies through the financing of pilot lines and early product validation and large-scale demonstration actions", has selected the Fake News project in the effort to support the technological development of tools to control information exchange on the Web to counter the phenomenon of disinformation.